Development Of Basic Attacking Technique Training Using The Feet In Teqball Games For Pjkr Students Of The Class Of 2025 - Kafi, Ashabul; Agusman, Muhammad; Sardiman, Sardiman; Purwanto, Didik; Saparia, Andi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study aims to develop a basic attack technique training model using the feet in Teqball for Physical education, health, and recreation (PJKR) students at Tadulako University. The research method used is Research and Development (R&D) with reference to the ten steps of Borg and Gall, including needs analysis, planning, initial product development, expert validation, revision, and phase I and II trials. The research subjects consisted of 15 students in the small group trial and 20 students in the large group trial, with the instrument being a rating scale questionnaire. The results of the phase I trial showed that several training models had met the feasibility criteria with a percentage range of 60%–77%, but several models needed to be revised because they were below 50%. After the revision, the phase II trial showed a significant improvement, where most models were in the “used” category with a percentage of 67%–98%. Validation by Teqball experts and learning experts also showed a high level of feasibility with a percentage of 67%–73%. Overall, the development of ten training models—ranging from two-touch attacks to reflex kicks—proved to be feasible and could be used as a learning and training tool to improve foot-attacking skills in Teqball.